Numerical investigation of geostress influence on the grouting reinforcement effectiveness of tunnel surrounding rock mass in fault fracture zones - Xiangyu Xu; Zhijun Wu; Lei Weng; Zhaofei Chu; Quansheng Liu; Yuan Zhou (Journal of Rock Mechanics and Geotechnical Engineering, 2024)
Grouting is a widely used approach to reinforce broken surrounding rock mass during the construction of underground tunnels in fault fracture zones, and its reinforcement effectiveness is highly affected by geostress. In this study, a numerical manifold method (NMM) based simulator has been developed to examine the impact of geostress conditions on grouting reinforcement during tunnel excavation. To develop this simulator, a detection technique for identifying slurry migration channels and an improved fluid-solid coupling (F–S) framework, which considers the influence of fracture properties and geostress states, is developed and incorporated into a zero-thickness cohesive element (ZE) based NMM (Co-NMM) for simulating tunnel excavation. Additionally, to simulate coagulation of injected slurry, a bonding repair algorithm is further proposed based on the ZE model. To verify the accuracy of the proposed simulator, a series of simulations about slurry migration in single fractures and fracture networks are numerically reproduced, and the results align well with analytical and laboratory test results. Furthermore, these numerical results show that neglecting the influence of geostress condition can lead to a serious overestimation of slurry migration range and reinforcement effectiveness. After validations, a series of simulations about tunnel grouting reinforcement and tunnel excavation in fault fracture zones with varying fracture densities under different geostress conditions are conducted. Based on these simulations, the influence of geostress conditions and the optimization of grouting schemes are discussed.